(untitled) (Pulse, 2022)
Rupture of the ventricular septum, a rare but potentially fatal complication of acute myocardial infarction, is usually observed in the setting of acute myocardial infarction associated with major coronary artery occlusion. It is often accompanied by severe circulatory failure. In this paper we describe a case of a 70-year-old lady who presented with cardiogenic shock 7 days after acute myocardial infarction and was found to have ventricular septal rupture. Pulse volumel.11 January-December 2018-2019 p.27-32